Reflections on the Neoclassical Dispositions of a Banned Playwright - Ellodi, Denise (Global Writing Academica Researching & Publishing, 2025)
The literary work of Albanian playwright Etëhem Haxhiademi had been banned for over four decades due to vindictive political principles. He was one of the most notable creators of Albanian tragedy, revealing Albanian literature in the modern era. In 1924, he wrote the tragedy